Estrogen regulates the expression and activity of epithelial sodium channel in mouse osteoblasts - Yang, G. Z.; Nie, H. G.; Lu, L.; Chen, J.; Lu, X. Y.; Ji, H. L.; Li, Q. N. (Cellular and Molecular Biology, 2011)
Estrogen plays an important role in bone metabolism and only high dose can stimulate osteoblast bone formation. However, the underlying mechanisms have not been elucidated. The epithelial sodium channel (ENaC) is a key pathway for sodium transport in epithelia, vascular endothelium, and other tissues; although the expressions of Î± and Î³ ENaC mRNA were found in osteoblasts, the regulation of ENaC by estrogen in osteoblasts has not been studied. Our recent data confirmed the ENaC expression in mouse primary osteoblasts by immunocytofluorescence, RT-PCR, western blot, and patch clamp. Furthermore, we found estrogen (10-5M) increased the expression of Î± and Î³ ENaC subunits at both the mRNA and protein levels in osteoblasts. On the other hand, 17Î²estradiol (20nM) increased inward Na+ currents which were inhibited by amiloride. The estrogen dose used in patch clamp is much lower than those of mRNA and protein analysis, which means single cell ENaC electrophoretic mobility is much more sensitive to estrogen than the mRNA and protein production by estrogen stimulation. Our results suggest that estrogen regulates expression and function of ENaC in osteoblasts may provide a new clue that the mechanism of high dose of estrogen influence osteoblast bone formation via ENaC activity.